2018
DOI: 10.1098/rspb.2018.0197
|View full text |Cite
|
Sign up to set email alerts
|

Calcium isotopes offer clues on resource partitioning among Cretaceous predatory dinosaurs

Abstract: Large predators are overabundant in mid-Cretaceous continental dinosaur assemblages of North Africa. Such unbalanced ecosystem structure involves, among predatory dinosaurs, typical abelisaurid or carcharodontosaurid theropods co-occurring with long-snouted spinosaurids of debated ecology. Here, we report calcium (Ca) isotope values from tooth enamel (expressed as Ca) to investigate resource partitioning in mid-Cretaceous assemblages from Niger (Gadoufaoua) and Morocco (Kem Kem Beds). In both assemblages, spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 37 publications
6
50
0
1
Order By: Relevance
“…The piscivorous habit of spinosaurs has been supported by oxygen isotopic values from bone apatite (Amiot et al 2010). Calcium isotopic values from tooth enamel extend these results, supporting resource partitioning among large theropods in both Kem Kem and Gadoufaoua faunas (Hassler et al 2018).…”
Section: Kem Kem Assemblagementioning
confidence: 74%
See 1 more Smart Citation
“…The piscivorous habit of spinosaurs has been supported by oxygen isotopic values from bone apatite (Amiot et al 2010). Calcium isotopic values from tooth enamel extend these results, supporting resource partitioning among large theropods in both Kem Kem and Gadoufaoua faunas (Hassler et al 2018).…”
Section: Kem Kem Assemblagementioning
confidence: 74%
“…Thus, the taxonomic and numerical predominance of predatory dinosaurs, which has been termed an "unbalanced food web" (Läng et al 2013), appears to be a real signal. These large-bodied theropods are supported primarily or secondarily by the abundance and availability of aquatic protein resources (Amiot et al 2010, Hassler et al 2018. The dissected deltaic plain and nearshore environments may have enhanced aquatic resources while limiting, or rendering patchy areas of available vegetation for large-bodied dinosaurian herbivores.…”
Section: Kem Kem Assemblagementioning
confidence: 99%
“…With 21 dental synapomorphies, the spinosaurid dentition is highly specialized, from the conical fluted crowns bearing minute or no denticles at all to the terminal rosette of the upper and lower jaw with subcircular alveoli (e.g., Charig and Milner, 1997;Sereno et al, 1998;Sues et al, 2002;Dal Sasso et al, 2005;Hendrickx and Mateus, 2014a;Sales and Schultz, 2017). Several studies have shown that these theropods were semi-aquatic animals feeding, at least partially, on fish (e.g., Charig and Milner, 1997;Rayfield et al, 2007;Amiot et al, 2010;Ibrahim et al, 2014;Hassler et al, 2018), suggesting that their peculiar dentition is linked to the specialized piscivorous diet.…”
Section: Major Evolutionary Transitions In the Non-avian Theropod Denmentioning
confidence: 99%
“…Isolated theropod teeth provide taphonomic, paleoenvironmental and paleoecological data (e.g., Briggs and Crowther, 2001;Amiot et al, 2004Amiot et al, , 2006Amiot et al, , 2009Amiot et al, , 2011Rogers et al, 2007;Fanti et al, 2014;Gerke and Wings, 2016;Hassler et al, 2018;Frederickson et al, 2018). They may also provide evidence for paleodiversity, biostratigraphy (i.e., temporal/geographic ranges of theropod taxa), and anatomical information on clades when articulated skeletal fossils are missing or poorly represented Larson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Charig & Milner (1997) accepted the idea of the new english spinosaurid Baryonyx walkeri as a fish eater, but preferred to keep the animal on shore. From an analysis of calcium isotopes in vertebrate teeth from mid-Cretaceous continental biotas of North Africa, Hassler et al (2018) found that spinosaurids had a strong freshwater food source signal. Additionally, Amiot et al (2010) , based on analyses of oxygen isotope ratios (δ 18 O p ) from biogenic apatites from a wide range of spinosaurid remains, proposed that spinosaurids spent extended periods in freshwater.…”
Section: Introductionmentioning
confidence: 99%